PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PERPAJAKAN, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PKB DAN BBNKB - Dharma, Gede Pani Esa (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
The purpose of this study was to determine the effect of taxpayer awareness , socialization taxation , compliance and quality of service to the taxpayer to pay motor vehicle tax ( PKB ) and the tax transfer tax motor vehicles ( BBNKB ) SAMSAT Office Denpasar on both simultaneously ( F test ) or partially ( t-test ) . Sampling was done by the method of incidental , the taxpayers who pay taxes PKB and BBNKB that happened to be found at the time the study was conducted . Respondents ( sample ) was determined by Slovin formula amounted to 100 people . This study used multiple linear regression analysis . The results showed that simultaneous awareness taxpayer , taxation socialization , and quality of service have a significant effect on tax compliance in paying taxes on CLA and BBNKB SAMSAT Denpasar office . Taxpayer awareness , socialization taxation , and quality services is partially significant effect on tax compliance in paying taxes on CLA and BBNKB SAMSAT Office Denpasar .
Keywords: taxpayer awareness, socialization taxation, quality of service, taxpayer compliance